(untitled) (Estudios de Historia de España, 2023)
The crisis of the summer of 1917 in Spain was the consequence of a growing social discontent, which spread to the sectors and forces that were outside of the Political System of the Restoration, exacerbated as a result of the First World War. The confluence of the Juntista movement, the Assembly of Parliamentarians and the labor movement (anarchsyndicalism and socialist), led to a general strike, which precipitated the crisis of the Restoration System and the turnismo System. With the use of historical methodology and discourse analysis techniques, the work approaches the perception of Diario de la Marina, a Cuban media in the beginning of the XX Century, about the events that took place in the old Hispanic metropolis, showing the viability of the use of the press as a historical source. The marked pro-monarchical and conservative character of this newspaper is expressed in the manipulation of the information it offers.